Investigating a threshold effect in twin deficit hypothesis: Evidence from the BRICS economies - Tochukwu Timothy Okoli; Devi D. Tewari; Kehinde Damilola Ileasanmi (Cogent Economics & Finance, 2021)
Over the years, empirical evidence on twin-deficit hypothesis has been inconsistent. While some support it, others affirm the prevalence of the Ricardian Equivalence. This study therefore examines a nonlinear/threshold relationship between the deficits among the BRICS economies using the Panel ARDL (1, 1) model with a quarterly data spanning from 2000q1 to 2019q4. The efficient estimator of PMG based on the Hausman test shows that twin divergence holds among the BRICS market up to a certain threshold beyond which the hypothesis holds. This suggests that BRICS countries face a dampening effect of fiscal/current deficits on their current account/fiscal deficits to a point after which further increases in either of the deficits will significantly raise the other. The static fixed effect technique and second-order U-shaped test reveal a consistent result. The speed of adjustment to long-run steady state for the current account deficits and the fiscal deficits models are 27.4 and 52.5 per cents respectively, at 5 per cent significance level. However, higher growth shocks and interest rate lead to divergence of the deficits while exchange rate and trade openness dampen it. Fiscal deepening and management within a bound were recommended as the panacea for twin-deficit problems.
Keywords: 330; BRICS economies; current account deficits; Fiscal deficit; panel ARDL